Improvement of Laying Hen Performance by Dietary Prebiotic Chicory Oligofructose and Inulin - Chen, Y.C.; Nakthong, C.; Chen, T.C. (International Journal of Poultry Science, 2005)
Sixty White Leghorn hens (57 wk of age) were selected and divided randomly into three groups with two birds per cage. Twenty birds were assigned to each of the following diet treatments: 1) basal diet (control); 2) basal diet with 1.0% (w/w) of an oligofructose-type commercial prebiotic supplementation (Raftifeed®OPS); and 3) basal diet containing 1.0% (w/w) inulin, which was administered as 1.3% (w/w) of a semipurified chicory root extract (Raftifeed®IPE). The feeding trial lasted for 28 d. Oligofructose and inulin increased (P<0.05) weekly egg production by 13.35% and 10.73%, respectively as compared to the control. The rapidly fermented (cecum) oligofructose and the slowly fermented inulin also increased (P<0.05) cumulative weekly egg weight per bird by 12.50% and 10.96%, respectively, as compared to the control. There were no significant (P>0.05) differences in average egg weight, feed consumption, or albumen quality during the extended storage among the treatments. Both prebiotics improved (P<0.05) the feed conversion ratio. No differences in the percentages of changes in live body weight (%) were recorded after a 4-wk feeding trial. Interestingly, both prebiotic supplementations elongated (P<0.05) small and large intestinal lengths. This concomitant increased absorption of capacity could be at the basis of the observations reported here. In conclusion, dietary oligofructose and inulin can increase (P<0.05) egg production and feed efficiency of layers without impairing egg quality.